Benefits of domperidone in ambulatory acute diarrhea with severe vomiting - Irene A. O.; Achirul Bakri; Erial Bahar; Rusdi Ismail (Paediatrica Indonesiana, 2007)
Background Recently, most patients with diarrheal disease (DD)cases are hospitalized not due to severe dehydration, but due tosevere vomiting which interferes with fluid and food intake. Useof anti-vomiting medicines is not recommended because of itsâ€œcentralâ€ side effects. Domperidone has prokinetic and antiemeticeffects with only minimal extrapyramidal side effects.Objective To evaluate domperidone in preventing hospitalizationof DD patients in outpatient setting.Methods This randomized double blind, placebo-controlledclinical trial, was conducted from February to August 2005 atMohammad Hoesin Hospital, Palembang. We included patientsaged 6 to 59 months old with acute diarrhea who had vomited atleast 4 times in the last 24 hours, not in need of hospitalization,and agreed to participate. We excluded patients who had takenanti-vomiting drug, or those who had severe diseases, includingsevere malnutrition. The dose of domperidone was 1.25 mg per 5kg body weight.Results There were 183 subjects randomized, consisted of 91 whotook domperidone (treatment group) and 92 who took placebo(control group). The duration and decrease of vomiting frequencywere significantly different in favor of domperidone. Domperidoneprevented hospitalization significantly (P=0.001, OR=4.1, ARR= 20%, RRR=71%, NNT=5). No overt acute clinical side effectswere found.Conclusion Domperidone significantly shortened the duration anddecreased the frequency of vomiting in DD cases.